Validação da nomenclatura de diagnósticos, resultados e intervenções de enfermagem para a Unidade de Terapia Intensiva geral do Hospital Universitário da UFPB - Ramos, Natana de Morais (2019)
Introduction: The validation of the Nomenclature for the General Intensive Care Unit (ICU) using the International Classification for Nursing Practice (CIPE®) is a fundamental step capable of evaluating its effectiveness during care practice and providing data that supports the decision-making process of the nurse, who when directed to the intensive care, can optimize the care provided. Objective: To validate the concepts contained in the Nomenclature of diagnoses, results and nursing interventions of CIPE® in the General ICU of HULW/UFPB. Method: This is a methodological research, developed in three stages: construction of operational definitions, validation of content and clinical diagnosis concepts, results and nursing interventions for the General ICU of the school hospital, carried out in May 2017 to April 2019. The Research Ethics Committee under opinion 2,605,425 and Certificate of Presentation approved this study for Ethical Appreciation (CAAE) n. 84367518.9.0000.5183. Results: A cross-mapping of 60 nursing diagnoses/results from the General ICU Nomenclature with CIPE® version 2017 was performed, resulting in 58 concepts, of which 38 (65.6%) were constant and 20 (34.4%) were non-constant in the classification. Operational definitions were constructed for the 58 concepts of diagnosis / nursing outcomes, and 57 concepts were validated in content using the consensus validation method. Then, seven clinical case studies weresubmitted to the clinical validation process, 41 diagnoses/results were validated, 23 (56.1%) included in the General ICU Nomenclature and 18 (43.9%) were non-constant. Regarding the interventions, 227 valid interventions were identified. Conclusion: Validation studies ofnursing diagnoses, results and interventions improve and operationalize the use of the Nomenclature during the care practice, generating higher quality care for people under intensive care.